Pengaruh Bimbingan Kelompok Dengan Teknik Symbolic Modelling Terhadap Self Efficacy Siswa Madrasah Ibtida'iyah’IYAH Darun Najah Bojonegoro - Mohamad Abdul Azis; Mohammad Muslih; Angga Nuraufa Zamzami Putra (Comprehensive Journal of Islamic Studies, 2024)
The Research aims to determine the effect of group guidance services using symbolic modeling techniques on the self-efficacy of Madrasah Ibtidaiyah Darun Najah Bojonegoro students. This research uses a quantitative experimental method, one group pretest-posttest design. The population of this research was Classes 1 and 2of Madrasah Ibtidaiyah Darun Najah Bojonegoro, totaling 30 students. The sampling technique used was total sampling and a sample of 6 students was obtained. Researchers used data collectors in the form of a Guttmant scale with 2 alternative answer choices, namely yes and no. In the research results, it is knownthat the posttest results of the experimental class which resulted in Madrasah Ibtidaiyahliki increasing in value compared to the average pretest score before being given 6 treatments was 58% and after being given treatment with symbolic modeling techniques, Madrasah Ibtidaiyah increased by 95% and the difference between the increases between pretests. and posttest of 57%. From the Wilxcon testusing SPSS version 22.00, the output results show a Sig value of 0.003 < 0.05, which means there is a difference between the preetest and posttest so that Ha is accepted, there is an influence of the symbolic modeling technique group guidanceservices on the self-efficacy of Madrasah Ibtidaiyah Darun Najah Bojonegoro students